HEALTH CARE LICENSING (Study on Implementation Services Practice License and Work Permit Health Workers in the District Health Office of East Kutai Based on Local Regulation No. 45 Year 2010 on Main Duties and Functions (TOR) and Job Description Structura - Sujito, Hadi Ernata; Ventura NGW, Dr. Bona; Jatmikowati, Dr. Sri Hartini (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Implementation Services licensing on Health Office is the government effort to meet the basic needs and civil rights of every citizen in the goods, services and administrative services provided by the delivery of public services. Reality shows that the condition of public services is still faced with a system of government that has not been effective and effesien and quality of human resources is not adequate apparatus. It is seen from the number of complaints and complaints from the public, both directly and through the mass media. Based on the description of the problems, the writer interested in conducting research on: Licensing Services Health Workers in the District Health Office of East Kutai To describe and analyze the advantages and barriers to implementation of License Practice (SIP) and Work Permit (SIK) Medicals. The research aimed to describe and analyze the Policy Implementation Services, the service model, as well as the advantages and barriers to SIP and SIK licensing service provided to the community. The results showed; No differentiation in the service of SIP service mechanisms and Work Permit (SIK) at the District Health Office of East Kutai, the design of the model licensing service designed to provide fast service, cheap and quality. The advantages and barriers to services is affected by communication, resources, disposition, bureaucratic structure and delegation of authority.